To Know Is To Be – Wisdom in Philosophy as a Way of Life and Its Implications for our Understanding of Knowledge - Lucas Nascimento Machado (Eidos. A Journal for Philosophy of Culture)
In my paper, I attempt to show how the Hadotian metaphilosophical perspective of philosophy as a way of life (PWL for short) implies another conception of what true, philosophical knowledge is: a conception that one should understand through Hadot’s reading of what is Sophia for ancient philosophy. To do so, I present my account of PWL according to Hadot as a way of understanding philosophy in which the way of life comes first and the discourse comes second and which is practiced fundamentally through the spiritual exercises of attention to the present moment and cosmic consciousness. Through this exposition, I show that the PWL conception of knowledge is one in which to know is to be that which is known. I then connect this discussion to contemporary philosophical debate and critique of our current society by Byung-Chul Han and Ailton Krenak, pointing out how the PWL conception of knowledge is relevant to that debate and, thus, crucial for the reflection on alternatives to the way we live today, led by demands of productivity and utility.